THE EFFECT OF PACKAGING COLOR SCHEME ON PERCEPTIONS, PRODUCT PREFERENCES, PRODUCT TRIAL, AND PURCHASE INTENTION - Wirania Swasty; Mediany Kriseka Putri; Mohammad Isa Pramana Koesoemadinata; Ahmad Nur Sheha Gunawan (Jurnal Manajemen dan Kewirausahaan, 2021)
This study aims to understand the effect of different color scheme in perceptions and food product preference, product trial, and purchase intention. Using quantitative approach, the questionnaires data were cross tested by chi square and one-way ANOVA. The study found there were no significant differences between the price perception, the perceived quality, product preferences, product trial and intense to buy in the different color schemes, except white dominant color in perceived quality aspect. Respondents assessed the use of monochrome color schemes tended to have higher price perceptions and higher quality than white, yellow, analog, and complementary color schemes. It is expected to be a reference to provide an understanding of packaging design strategy especially food products by using color scheme. Keywords: Color scheme, packaging, product preference, perception, SME.